Approaching the quantum critical point in a highly correlated all-in-all-out antiferromagnet - Wang, Y; Rosenbaum, TF; Prabhakaran, D; Boothroyd, AT; Feng, Y (American Physical Society, 2020)
Continuous quantum phase transition involving all-in-all-out (AIAO) antiferromagnetic order in strongly spin-orbit-coupled 5d compounds could give rise to various exotic electronic phases and strongly-coupled quantum critical phenomena. Here we experimentally trace the AIAO spin order in Sm2Ir2O7 using direct resonant X-ray magnetic diffraction techniques under high pressure. The magnetic order is suppressed at a critical pressure Pc=6.30GPa, while the lattice symmetry remains in the cubic Fd-3m space group across the quantum critical point. Comparing pressure tuning and the chemical series R2Ir2O7 reveals that the approach to the AIAO quantum phase transition is characterized by contrasting evolutions of the pyrochlore lattice constant a and the trigonal distortion surrounding individual Ir moments, which affects the 5d bandwidth and the Ising anisotropy, respectively. We posit that the opposite effects of pressure and chemical tuning lead to spin fluctuations with different Ising and Heisenberg character in the quantum critical region. Finally, the observed low pressure scale of the AIAO quantum phase transition in Sm2Ir2O7 identifies a circumscribed region of P-T space for investigating the putative magnetic Weyl semimetal state.